Socialization Of Bullying As A Prevention Effort Violence Occurred In Primary Schools - Rafida Azzahra Prasetyo Putri (Universitas Sahid Surakarta, 2025)
AbstractPrevention of bullying socialization violence in schools can be done, among other things, by monitoring nd providing appropriate sanctions to the perpetrators. Data collection methods in this service are observation, teaching and lectures, one way is by incorporating bullying material into learning which will have a positive impact on students' personal development. The aim of this research is to understand the role of schools in preventing acts of bullying violence at SD Muhammadiyah PK Baturan. This research design is qualitative with a phenomenological approach. Research participants are the school community consisting of school principals and teachers. The sampling technique used was purposive sampling. The number of participants was 56 and 7 people experienced bullying after finding data saturation. The research results showed that prevention of bullying incidents has been carried out with various programs such as supervision, counseling and character education which have so far proven to be effective. Conclusion: from the service carried out by the resource person, it can be explained that the school gave a good response. Keywords: bullying, elementary school